Understanding key constraints and practice design in Rugby Union place kicking: Experiential knowledge of professional kickers and experienced coaches. Issue 5 (December 2020) - Pocock, Chris; Bezodis, Neil E; Davids, Keith; Wadey, Ross; North, Jamie S
Place kicks present valuable opportunities to score points in Rugby Union, which are typically performed under varying constraints in competitive performance environments. Previous quantitative studies suggest these interacting constraints can influence fluctuations in place kick success. To further the understanding of how fluctuations in place kicking success emerge, our aim was twofold: i) to explore and identify the key constraints that professional place kickers and experienced place kicking coaches perceive to influence the difficulty of a place kick and ii) to understand the level to which current place kicking practice environments represent these key constraints experienced in performance environments. Six professional place kickers and six experienced place kicking coaches were interviewed. Using a deductive thematic analysis, 11 key constraints were identified: individual constraints of expectation for success and fatigue, task constraints of angle and distance to goalposts, environmental constraints of wind, weather, pitch, and crowd, and situational constraints of previous kicking performance, time remaining and current score margin. Place kicking is typically practised individually or with a small number of place kickers in isolation from team sessions. Where possible, coaches should be encouraged to include place kicking in simulated game scenarios during practice to represent key constraints from performance environments. Our study demonstrates how experiential knowledge can enrich the understanding of sport performance and inform the design of practice environments which simulate relevant constraints of competitive performance to enhance skill adaptation of athletes.